Performance of citrus rootstocks in the presence of aluminum. - Nogueira, Sandra dos Santos S.; Nagai, Violeta; Carelli, Maria Luiza Carvalho; Fahl, Joel Irineu (Pesquisa Agropecuaria Brasileira, 2014)
With the objective of evaluating the performance of Rangpur lime, Volkameriano lemon, Orlando tangelo, and Sunki tangerine citrus rootstock cultivars, using different aluminum concentrations, an experiment was conducted in a split-plot design, in greenhouse of the Seção de Fisiologia do Instituto Agronômico de Campinas, SP, Brazil, with aluminum levels of 0 ppm, 15 ppm, 30 ppm and 60 ppm, as ALK (SO4)2. 12H2O in nutritive solution. Growth data and macro and micronutrient levels in leaves and roots were analysed. It was observed that the aluminum affected the root length of all cultivars. The plant height and the dry matter weight of leaves and roots of Sunki and Rangpur lime cultivars were negatively affected by aluminum. The increasing dosage of aluminum reduced the leaf absorption of phosphorus and calcium and increased the potassium for all cultivars. In general, the cultivar Orlando had a better tolerance for aluminum than the other cultivars, so it is suggested for citrus cultivation in acid soils.